الخط العربي – نشأته وخصائصه وكيفية تطوره - أمين عليوة; خديجة بن قويدر (Universitas Negeri Malang, 2022)
Arabic calligraphy is one of the arts full of beauty, and it is one of the civilizational manifestations that Muslims have concerned with since the beginning of Islam, especially because it is closely related to the Holy Qur’an, and it was written down in order to preserve it for future generations after the spread of melody among the parish, and Arabic calligraphy has witnessed a great development throughout history. Especially in the early days of Islam and beyond, where they were interested in writing letters and the means that preserved the Holy Qur’an, and it coincided with the great renaissance witnessed by the Islamic nation in various aspects of life, and the latter received a distinct interest in being. And that was during the era of Caliph Othman bin Affan, may God be pleased with him. This leads us to ask a set of questions, what is Arabic calligraphy? How has it evolved through the ages and who are the most famous and skilled calligraphers? What are the types of Arabic calligraphy? What are its characteristics and advantages? We try to answer the previous problems, showing the aesthetics of Arabic calligraphy and its decorations, which enchanted the eyes.